Buffering – Please Be Patient! Does the Attribution of Pauses to Technical Issues Hamper Learning? - Merkt, Martin (Frontiers in Psychology, 2021)
In educational contexts, system-determined pauses are often used to interrupt the transient flow of information and thus avoid cognitive overload in dynamic learning materials. However, next to these didactically motivated interruptions, video-based learning materials may also be interrupted due to technical issues with regard to constrained bandwidth or outdated technology. Against this background, the current experiment investigated whether the interruption of dynamic representations due to technical issues negatively affects learning. For this purpose, 64 participants watched an Arabic language tutorial. They were either informed that the video included breaks in order to support learning or that there may be breaks due to technical issues. Contrary to our pre-registered hypotheses, the attribution of the pauses to technical issues did not hamper learning and did not affect participants’ ratings regarding the usefulness and the disturbance caused by the pauses. However, exploratory analyses revealed a negative correlation between the perceived usefulness and the disturbance caused by the pauses. Limitations and implications of these findings are discussed.